Knowledge, Attitude, and Behavior of Pakistani Population Toward Hepatitis B and Associated Factors - Ishtiaq, Hifza; Zafar, Alina; Kant, Bashir ur Rehman; Ahmed, Saqlain; Raja, Ayesha Ijaz; Khattak, Iftikhar (Indus Journal of Bioscience Research, 2024)
Background: Hepatitis B is the liver’s infection transmitted through the HB virus. The infection can be in acute or chronic form. Objective: The study objectives were to find the knowledge, attitude, and behavior of the Pakistani population regarding hepatitis B and associated risk factors. Methodology: This was a cross-sectional research study. The research study included 385 respondents with a level of confidence of 95% and less than 5 percent margin of error. Data were collected by sending Google Forms links through all social media platforms, such as WhatsApp and Facebook, which are widely used in Pakistan. The data were then transferred to SPSS Statistics version 25.0. The significance of the association was determined using p-values. The ordinal logistic regression analysis was applied to confirm the relationship of demographic factors with KAB. Result: Out of 385 participants most respondents were aged between 30 and 49 years (41.6%). Most of the participants correctly identified that Hepatitis B is caused by a virus (65.0%) and can be transmitted via blood (75.3%). Age demonstrated a significant effect, with individuals aged 50 years or older being about 1.8 higher probability to have better knowledge levels compared to those aged 18–29 years (Odds ratio: 1.8, 95% Confidence Interval (CI): 1.2–2.7, p = 0.003). Level of education significantly influenced attitudes, with individuals having higher education demonstrating over twice the likelihood of a positive attitude compared to those with no formal education (Odds ratio (OR): 2.1, 95% Confidence Interval: 1.5 to 3.0, p-value < 0.001). Conclusion: Higher knowledge and positive attitudes, influenced by age, education, and urban residence, strongly correlated with improved health behaviors.